Dove (The Biblical archaeology review, 2022)
Across history and cultures, the dove is a universal symbol of peace and tranquility. Its several species belong to the bird family columbidae, which also includes pigeons. In biblical tradition, the dove first appears in the story of the flood (Genesis 8). When the dove (Hebrew: yonah) released from Noah’s ark returns with an […]